Status of Anxiety among Health Care Professionals during Covid-19 Pandemic: Comparison of Two Different Mental Health Screening Tools to Detect Anxiety - Samal, Anup Mangal; Thapa, Niresh; Panta, Prem Prasad (Journal of Karnali Academy of Health Sciences, 2020)
Background: COVID-19 outbreak has the potential to significantly affect the mental health of health care professionals (HCPs) who stand in the frontline of this crisis. The aim of this study is to determine the prevalence of anxiety among HCPs in Karnali Academy of Health Sciences (KAHS) during the COVID-19 pandemic through the use of two commonly used screening tools: Becks Anxiety Inventory (BAI) and Hospital Anxiety and Depression Scale- Anxiety Subscale (HADS-A).Methodology: Hospital based descriptive cross-sectional study conducted in KAHS during the first half of October, 2020. Convenient sampling technique among HCPs was used. A 21-item BAI and a 7-item HADS-A were used to collect the data. For each of the questions, responses were rated on a 4-point Likert scale that ranged from zero (not at all) to three (severely).Results: A total of 75 HCPs participated in the study. Over-all prevalence of anxiety was found at 38.7% by BAI tool versus 33.3% by HADS-A (mean 36% percentage). Nurses reported the highest level of anxiety that was statistically significant (p